Experimental investigation on flow patterns and absorption height in a vertical bubble absorber with R124-NMP pair and comparison for R124-DMAC pair. (5th March 2020) - Wang, Wei; Xu, Shiming; Wu, Xi; Jin, Dongxu; Jiang, Mengnan
Highlights: Three typical flow patterns of R124-NMP bubble absorption process are captured. The DAH changes almost linearly as the dimensionless operation parameters vary. The AH of R124-NMP is lower than that of R124-DMAC under the same conditions. Correlations of AH and DAH were developed to predict the bubble absorption height. Abstract: A visual experimental research was conducted to investigate the flow patterns and absorption height (AH) in a vertical bubble absorption tube employing R124-NMP as working fluid. The effects of various operation parameters, solution inlet mass concentration, temperature and volumetric flow rate, vapor volumetric flow rate, absorption pressure and orifice diameter, on the flow patterns and AH were examined. The key operation parameters were all converted into dimensionless numbers and the influences of dimensionless operation parameters on dimensionless absorption height (DAH) were studied. The results showed that the AH increases with increasing solution inlet mass concentration and temperature, vapor volumetric flow rate and orifice diameter and decreases with increasing solution volumetric flow rate and absorption pressure. DAH exhibits nearly linear change along with dimensionless operation parameters. Comparisons between the flow patterns and AH of R124-NMP and R124-DMAC were performed. The compared results illustrated that employing R124-NMP as working fluid can shrink the vertical bubble absorber size. Finally, the experimental correlations of AH and DAH were developed with ±20% and ±15% error bands, respectively. The correlation of DAH maybe used to predict absorption height in the design of bubble absorber employing refrigerant-organic absorbent as working fluid.